Fusing Educational Reform Policy and Action: Assuring the Development of Local Leaders - Marnik, George; Donaldson, Gordon (Maine Policy Review, 1994)
School change does not happen in a vacuum. It requires initiative and leadership. Because Maine’s educational system features a strong local control component, successful educational change requires development of local leadership. George Marnik and Gordon Donaldson report on the Maine Academyfor School Leaders, an educational leadership development project in which they were involved. Among other things, the researchers learned that successful educational change is not likely to result from a one-size-fits-all state policy. Rather, successful reform occurs "one individual at a time, one school at a time."